ChemInform Abstract: Perovskite Oxides: Preparation, Characterizations, and Applications in Heterogeneous Catalysis. Issue 44 (4th November 2014) - Zhu, Junjiang; Li, Hailong; Zhong, Linyun; Xiao, Ping; Xu, Xuelian; Yang, Xiangguang; Zhao, Zhen; Li, Jinlin
Abstract Review: 284 refs.